2006
DOI: 10.1111/j.1440-1819.2006.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of antistigma education on the attitudes of general practitioners regarding schizophrenia*

Abstract: The aim of this study was to examine the views and attitudes of general practitioners (GP) with respect to schizophrenia, and the changes in their attitudes after antistigma education. A total of 106 GPs working in 71 health institutions were included in the study. A questionnaire of 16 items, focussing on doctors' views and attitudes towards schizophrenia, was applied. Questions were about the views and attitudes of doctors towards general myths related to schizophrenia. Doctors were asked to select one of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 22 publications
0
46
0
4
Order By: Relevance
“…In seven studies, stigma was explicitly addressed in this theoretical introduction. As an example, Ucok et al (2006) described their intervention as follows: “the slide presentation lasted approximately 45 minutes and included current information on the course of schizophrenia and its treatment, the impact of stigma on schizophrenia, and description of GPs’ roles” (p. 440).…”
Section: Resultsmentioning
confidence: 99%
“…In seven studies, stigma was explicitly addressed in this theoretical introduction. As an example, Ucok et al (2006) described their intervention as follows: “the slide presentation lasted approximately 45 minutes and included current information on the course of schizophrenia and its treatment, the impact of stigma on schizophrenia, and description of GPs’ roles” (p. 440).…”
Section: Resultsmentioning
confidence: 99%
“…Stigmatisation of patients with SMD by GPs has also been reported as a hindering factor (e.g. GPs' fear of patient crisis and psychotic disorders) [66]. …”
Section: Discussionmentioning
confidence: 99%
“…The results of this study highlight that there may be a need to provide some GPs with training on clinical features of schizophrenia and education about stigma and its effects on health (Ucok et al, 2006). Based on the findings of this study, we are planning educational initiatives to provide GPs with information on the experience of psychosis, actual rates of recovery, risks of dangerous behaviours, and effectiveness of both drug and psychological treatments for this problem and to sensitise them to stigma.…”
Section: Sierpina Forys and Clarridge 2008) And Continuous Medical Ementioning
confidence: 99%
“…Suboptimal health care for PWS may be related to some physicians' limited knowledge of this disorder, and/or negative attitudes towards people with severe mental health problems (Solar, 2002;Liggins & Hatcher, 2005;Ucok et al, 2006;. Studies have revealed that physicians sometimes do not take the medical needs of PWS seriously, and that they tend to associate patient's physical complaints with mental illness (Shefer, Henderson, Howard, Murray, & Thornicroft, 2014) and to underestimate medical symptom severity (Thornicroft, Rose, & Kassam, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation